Computed tomography-derived parameters of myocardial morphology and function in black and white patients with acute chest pain - Takx, Richard A. P.; Apfaltrer, Paul (The American journal of cardiology, 2016)
Blacks have higher mortality and hospitalization rates because of congestive heart failure compared with white counterparts. Differences in cardiac structure and function may contribute to the racial disparity in cardiovascular outcomes. Our aim was to compare computed tomography (CT)-derived cardiac measurements between black patients with acute chest pain and age- and gender-matched white patients. We performed a retrospective analysis under an institutional review board waiver and in Health Insurance Portability and Accountability Act compliance. We investigated patients who underwent cardiac dual-source CT for acute chest pain. Myocardial mass, left ventricular (LV) ejection fraction, LV end-systolic volume, and LV end-diastolic volume were quantified using an automated analysis algorithm. Septal wall thickness and cardiac chamber diameters were manually measured. Measurements were compared by independent t test and linear regression. The study population consisted of 300 patients (150 black-mean age 54 ± 12 years; 46% men; 150 white-mean age 55 ± 11 years; 46% men). Myocardial mass was larger for blacks compared with white (176.1 ± 58.4 vs 155.9 ± 51.7 g, p = 0.002), which remained significant after adjusting for age, gender, body mass index, and hypertension. Septal wall thickness was slightly greater (11.9 ± 2.7 vs 11.2 ± 3.1 mm, p = 0.036). The LV inner diameter was moderately larger in black patients in systole (32.3 ± 9.0 vs 30.1 ± 5.4 ml, p = 0.010) and in diastole (50.1 ± 7.8 vs 48.9 ± 5.2 ml, p = 0.137), as well as LV end-diastolic volume (134.5 ± 42.7 vs 128.2 ± 30.6 ml, p = 0.143). Ejection fraction was nonsignificantly lower in blacks (67.1 ± 13.5% vs 69.0 ± 9.6%, p = 0.169). In conclusion, CT-derived myocardial mass was larger in blacks compared with whites, whereas LV functional parameters were generally not statistically different, suggesting that LV mass might be a possible contributing factor to the higher rate of cardiac events in blacks.
Gesehen am 08.02.2019